Polyurethane pouring sealant as well as preparation method and application thereof
By modifying the polymerization reaction of components such as castor oil polyether polyol and isocyanate, combined with nanomaterials, polyurethane potting glue with excellent shear bonding strength and moisture resistance are prepared, and the polyurethane potting glue in the prior art is solved The shortcomings in rapid curing, bonding strength and moisture and heat resistance meet the high-performance needs of new energy vehicles and complex electronic products.
Patent Information
- Application Number
- CN202411346907.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-31
AI Technical Summary
The existing polyurethane potting glue has shortcomings in rapid curing, bonding strength, moisture and heat resistance and service life, and it is difficult to meet the high-performance needs of new energy vehicles and complex electronic products.
Polyurethane potting glue with excellent shear bonding strength and moisture resistance is prepared by polymerization and transesterification reaction, combining nano calcium carbonate and trimethoxysilane and other materials. , ensure rapid curing and high adhesion of the colloid.
It realizes rapid curing of polyurethane potting adhesive, excellent shear bonding strength, good thermal conductivity and moisture and heat resistance, extends the service life of the appliance, and is suitable for the bonding needs of home decoration and electronic products.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyurethane adhesives, and in particular relates to a polyurethane potting adhesive and a preparation method and application thereof. Background Art
[0002] Adhesives are mainly divided into polyurethane, silicone, epoxy resin and silane-modified polyether. In the past few decades, the demand for adhesives with high modulus and excellent adhesion for some composite substrates has been growing. At the same time, the characteristics of adaptability, moisture and heat resistance, service life and operability must also be considered. In terms of potting glue, it is mainly divided into three categories: epoxy resin, silicone and polyurethane. Epoxy resin potting glue has excellent high temperature resistance and electrical insulation ability. After curing into a colloid, it has a high hardness and is brittle. It is difficult to remove, has good confidentiality and poor moisture resistance. Silicone potting glue has strong anti-aging ability, good weather resistance, and excellent impact resistance, but the price is high, the adhesion is poor, and the mechanical strength is not high. Polyurethane potting glue can control the ratio and structure of the soft segment and the hard segment in the molecular chain to make the system have good flexibility and avoid the disadvantage of easy brittleness. There are more and more cases of using polyurethane-based glue to meet the required performance, but ordinary polyurethane potting glue has many problems and is not enough to be applied to complex scenes. Therefore, it is necessary to develop polyurethane potting adhesives with excellent shear bond strength performance for use in various consumer electronic products as well as automotive, aerospace and other industries involving electronic assembly.
[0003] At present, with the boom in the electric vehicle industry, there is an increasing demand for the development and production of new energy vehicles, especially for automotive adhesives and battery adhesives, which have put forward higher performance, environmental protection and safety requirements. It is necessary to seek high mechanical properties to meet its bonding, and also consider the heat dissipation of battery charging and discharging, as well as subsequent aging cleaning and recycling. In addition, the use of adhesives should also give priority to its safety performance, improve heat resistance, corrosion resistance, moisture resistance and other properties, so the selection of raw materials for potting adhesives is extremely important. Castor oil is simple in source, low in price, and is a renewable resource, which greatly reduces the economic cost of enterprises, but pure castor oil-based polyurethane potting adhesives have the defects of slow curing speed, low bonding strength and poor moisture and heat resistance. Summary of the invention
[0004] The purpose of the present invention is to provide a polyurethane potting adhesive and a preparation method and application thereof. The polyurethane potting adhesive provided by the present invention can be quickly cured in a short time, provides excellent shear bonding strength for rapid bonding to prevent falling off, does not foam, has uniform glue formation, can quickly conduct heat to increase the service life of electrical appliances, and also has good moisture and heat resistance. In addition, it also has good thixotropic properties and can be applied on walls or floors to meet the bonding and lamination requirements of home decoration tiles or floors.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a polyurethane potting adhesive, comprising independently packaged component A and component B;
[0007] The component A comprises the following raw materials in parts by weight: 10-20 parts of modified castor oil polyether polyol, 30-50 parts of castor oil, 10-25 parts of bisphenol A polyether polyol, 0.5-1.2 parts of dewatering agent, 10-20 parts of nano calcium carbonate, 0.01-0.05 parts of defoaming agent, and 0.05-0.1 parts of catalyst; the modified castor oil polyether polyol is obtained by reacting castor oil polyoxypropylene ether with mercaptoethanol and glycerol in sequence;
[0008] The component B comprises the following raw materials in parts by mass: 30-50 parts of isocyanate, 30-50 parts of polypropylene glycol, 0.5-2 parts of trimethoxysilane, 5-10 parts of fumed silica, and 0.5-1 part of flame retardant.
[0009] Preferably, the mass ratio of component A to component B is 1:(1-1.2).
[0010] Preferably, the hydroxyl value of the modified castor oil polyether polyol is 480-500 mgKOH / g; the preparation method of the modified castor oil polyether polyol comprises the following steps:
[0011] Castor oil polyoxypropylene ether, mercaptoethanol and azo initiator are mixed to carry out polymerization reaction to obtain a mercapto-modified product;
[0012] The mercapto-modified product, glycerol and an inorganic base compound are mixed to carry out an ester exchange reaction to obtain the modified castor oil polyether polyol.
[0013] Preferably, the water content of the castor oil polyoxypropylene ether is less than 0.05%, the mass ratio of the castor oil polyoxypropylene ether to mercaptoethanol is 5:1, and the mass ratio of the castor oil polyoxypropylene ether to mercaptoethanol is (1-5):1; the azo initiator is azobisisobutyronitrile, and the mass ratio of the castor oil polyoxypropylene ether to the azo initiator is (1-10):1; the temperature of the polymerization reaction is 110±5°C, and the time is 3±0.5h.
[0014] Preferably, the mass ratio of the castor oil polyoxypropylene ether to the glycerol is (1-5):1; the inorganic base is an alkali metal hydroxide; the temperature of the transesterification reaction is 150±5° C., and the time is 2±0.5 h.
[0015] Preferably, the hydroxyl value of the castor oil is 150-170 mgKOH / g;
[0016] The bisphenol A polyether polyol has a hydroxyl value of 223 to 233 mgKOH / g;
[0017] The dewatering agent includes p-toluenesulfonic acid isocyanate and / or vinyl trimethoxy silane;
[0018] The particle size D of the nano calcium carbonate 50 0.05~0.1μm, oil absorption value is 25~35;
[0019] The defoamer includes BYK A535;
[0020] The catalyst includes a cyclic amine catalyst or a tin laurate catalyst.
[0021] Preferably, the isocyanate includes one or more of diphenylmethane diisocyanate, toluene diisocyanate, hexamethylene diisocyanate, decamethylene diisocyanate, dodecane diisocyanate, 1,4-cyclohexane diisocyanate, 2,4-methylcyclohexane diisocyanate, isophorone diisocyanate and polymethyl polyphenyl isocyanate;
[0022] The polypropylene glycol is PPG8000;
[0023] The trimethoxysilane includes SilquestA-Link 597 silane and / or trimer silane;
[0024] The fumed silica is hydrophobic Evonik Aerosil R202;
[0025] The flame retardant includes inorganic flame retardant and / or organic flame retardant; the inorganic flame retardant includes aluminum hydroxide and / or magnesium hydroxide; the organic flame retardant includes melamine and alkyl phosphate organic matter.
[0026] The present invention provides a method for preparing the polyurethane potting adhesive described in the above technical solution, and the preparation method of component A comprises the following steps:
[0027] The modified castor oil polyether polyol, castor oil, bisphenol A polyether polyol, dewatering agent, nano calcium carbonate, defoaming agent and catalyst are first mixed, and then polymerization reaction and curing are carried out in sequence under a first vacuum condition to obtain the component A;
[0028] The preparation method of component B comprises the following steps:
[0029] The isocyanate, polypropylene glycol, trimethoxysilane, fumed silica and flame retardant are mixed for a second time under a second vacuum condition to obtain component B.
[0030] Preferably, the vacuum degree of the first vacuum condition and the second vacuum condition is ≤-98 kPa; the temperature of the polymerization reaction and curing is room temperature, and the time is 80 to 90 minutes;
[0031] The temperature of the second mixing is ≤40° C. and the time is 20 to 30 minutes.
[0032] The present invention provides the use of the polyurethane potting adhesive described in the above technical solution or the polyurethane potting adhesive prepared by the preparation method described in the above technical solution in the fields of adhesive for electrical appliances, adhesive for transportation vehicles, adhesive for batteries or adhesive for home decoration.
[0033] The invention provides a polyurethane potting adhesive, comprising independently packaged component A and component B; the component A comprises the following raw materials in parts by mass: 10-20 parts of modified castor oil polyether polyol, 30-50 parts of castor oil, 10-25 parts of bisphenol A polyether polyol, 0.5-1.2 parts of dewatering agent, 10-20 parts of nano calcium carbonate, 0.01-0.05 parts of defoaming agent, and 0.05-0.1 parts of catalyst; the modified castor oil polyether polyol is obtained by reacting castor oil polyoxypropylene ether with mercaptoethanol and glycerol in sequence; the component B comprises the following raw materials in parts by mass: 30-50 parts of isocyanate, 30-50 parts of polypropylene glycol, 0.5-2 parts of trimethoxysilane, 5-10 parts of fumed silica, and 0.5-1 parts of flame retardant. In the present invention, the modified castor oil polyether polyol in the raw material of component A contains active hydroxyl (-OH) and thiol (-SH) in the structure, wherein the active hydroxyl and thiol are active groups that can participate in chemical reactions. The presence of the -SH group transfers the active center of the carbon-carbon double bond of the castor oil molecule, thereby reducing the reaction between the castor oil molecule and the water molecule and improving its resistance to moisture and heat. On the other hand, the structure contains more S elements, which can increase the flame retardant properties of the product. At the same time, the number of -OH in the modified castor oil polyether polyol chain segment is increased after modification by glycerol, providing more reaction sites to increase the crosslinking density of the polymer, and improving the strength of the network structure formed by subsequent polymerization. At the same time, the polyether chain segment provides the required softness for the polyurethane glue. In addition, because it is a derivative product of castor oil, it can also increase the corrosion resistance of the product. The bisphenol A polyether polyol in the raw material of component A provides the required adhesion and certain mechanical stability for the polyurethane potting glue, and improves the moisture resistance of the glue. The trimethoxysilane in the raw material of component B is mainly composed of trimethoxysilyl and isocyanurate structures, which can effectively improve the adhesion to various substrates, wet the substrate well, and provide the necessary heat resistance (still good under 200°C) and low volatility, thereby improving the moisture and heat resistance of the polyurethane potting glue. In summary, the present invention controls the types and mass ratios of the raw materials of component A and component B, and the obtained polyurethane potting glue can be quickly cured in a short time, provides excellent shear bonding strength for rapid bonding to prevent falling off, and will not foam, and the glue is uniform, and can quickly conduct heat to increase the service life of the electrical appliance. It also has good moisture and heat resistance. In addition, it also has good thixotropic properties for gluing on walls or floors, meeting the bonding and fitting requirements of home decoration tiles or floors. DETAILED DESCRIPTION
[0034] The present invention provides a polyurethane potting adhesive, comprising independently packaged component A and component B;
[0035] The component A comprises the following raw materials in parts by weight: 10-20 parts of modified castor oil polyether polyol, 30-50 parts of castor oil, 10-25 parts of bisphenol A polyether polyol, 0.5-1.2 parts of dewatering agent, 10-20 parts of nano calcium carbonate, 0.01-0.05 parts of defoaming agent, and 0.05-0.1 parts of catalyst; the modified castor oil polyether polyol is obtained by reacting castor oil polyoxypropylene ether with mercaptoethanol and glycerol in sequence;
[0036] The component B comprises the following raw materials in parts by weight: 30-50 parts of isocyanate, 30-50 parts of polypropylene glycol, 0.5-2 parts of trimethoxysilane, 5-10 parts of fumed silica, and 0.5-1 part of flame retardant.
[0037] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.
[0038] The polyurethane potting adhesive provided by the present invention comprises an independently packaged component A. The component A comprises the following raw materials in parts by weight: 10 to 20 parts of modified castor oil polyether polyol, 30 to 50 parts of castor oil, 10 to 25 parts of bisphenol A polyether polyol, 0.5 to 1.2 parts of dewatering agent, 10 to 20 parts of nano calcium carbonate, 0.01 to 0.05 parts of defoaming agent, and 0.05 to 0.1 parts of catalyst; the modified castor oil polyether polyol is obtained by reacting castor oil polyoxypropylene ether with mercaptoethanol and glycerol in sequence.
[0039] In parts by mass, the component A comprises 10 to 20 parts of modified castor oil polyether polyol, and is preferably 15, 18, 12, 20 or 10 parts. In the present invention, the hydroxyl value of the modified castor oil polyether polyol is preferably 480 to 500 mgKOH / g.
[0040] In the present invention, the preparation method of the modified castor oil polyether polyol preferably comprises the following steps:
[0041] Castor oil polyoxypropylene ether, mercaptoethanol and azo initiator are mixed to carry out polymerization reaction to obtain a mercapto-modified product;
[0042] The mercapto-modified product, glycerol and an inorganic base compound are mixed to carry out an ester exchange reaction to obtain the modified castor oil polyether polyol.
[0043] The present invention mixes castor oil polyoxypropylene ether, mercaptoethanol and azo initiator for polymerization reaction to obtain a thiol-modified product. The castor oil polyoxypropylene ether is preferably purchased from the castor oil polyether series products of Zhejiang Huangma Technology Co., Ltd. The water content of the castor oil polyoxypropylene ether is preferably <0.05%. Before the mixing, the present invention preferably performs a pre-dehydration treatment on the castor oil polyoxypropylene ether. The mass ratio of the castor oil polyoxypropylene ether and mercaptoethanol is preferably (1-5):1, and specifically preferably 5:1. The azo initiator is specifically preferably azobisisobutyronitrile, and the mass ratio of the castor oil polyoxypropylene ether and the azo initiator is preferably (1-10):1, and specifically preferably 10:1. The temperature of the polymerization reaction is 110±5°C; the time is preferably 3±0.5h. In the present invention, when the polymerization reaction temperature is lower than 100°C, the reaction will not proceed sufficiently and the desired conversion rate will not be achieved. If the time is too short, the yield of the product will decrease, and the obtained thiol-modified product will not be effectively modified. Therefore, the polymerization reaction temperature in the present invention is preferably 110±5°C, and the time is preferably 3h±0.5h.
[0044] After obtaining the thiol-modified product, before carrying out the transesterification reaction, the present invention preferably pre-dries the thiol-modified product.
[0045] After obtaining the dried thiol-modified product, the present invention mixes the thiol-modified product, glycerol and an inorganic base compound to carry out an ester exchange reaction to obtain the modified castor oil polyether polyol. In the present invention, the mass ratio of the castor oil polyoxypropylene ether and the glycerol is preferably (1-5):1, and specifically preferably 5:1. The inorganic base is preferably an alkali metal hydroxide, and specifically preferably potassium hydroxide. The present invention has no special requirements for the amount of the inorganic base, and it is sufficient to ensure that the thiol-modified product and glycerol smoothly carry out the ester exchange reaction in an alkaline environment. The temperature of the ester exchange reaction is preferably 150±5°C, and the time is preferably 2±0.5h. In the present invention, the temperature of the ester exchange reaction must reach about 150°C to effectively allow the reaction raw materials to react, so the temperature of the ester exchange reaction in the present invention is 150±5°C, and the time is 2±0.5h.
[0046] Based on the mass fraction of the modified castor oil polyether polyol, the component A comprises 30 to 50 parts of castor oil, preferably 25 to 50 parts, and more preferably 45 parts, 42 parts, 48 parts, 40 parts or 36 parts. In the present invention, the hydroxyl value of the castor oil is 150 to 170 mgKOH / g.
[0047] Based on the mass fraction of the modified castor oil polyether polyol, the component A includes 10 to 25 parts of bisphenol A polyether polyol, preferably 20 parts, 15 parts or 25 parts. In the present invention, the hydroxyl value of the bisphenol A polyether polyol is preferably 223 to 233 mgKOH / g. The present invention selects bisphenol A polyether polyols with a hydroxyl value of preferably 223 to 233 mgKOH / g to provide the required adhesion and mechanical stability for the polyurethane potting glue, thereby improving the moisture resistance of the polyurethane potting glue. In a specific embodiment of the present invention, the bisphenol A polyether polyol is a propylene oxide alkylation product of bisphenol A, preferably a bisphenol A polyether polyol of Zhejiang Huangma Technology Co., Ltd. In the present invention: the bisphenol A polyether polyol provides the required adhesion and certain mechanical stability for the polyurethane potting glue, and improves the moisture resistance of the glue.
[0048] Based on the mass fraction of the modified castor oil polyether polyol, the component A includes 0.5 to 1.2 parts of a dewatering agent, and is preferably 0.8 parts, 1 part or 1.2 parts. In the present invention, the dewatering agent preferably includes p-toluenesulfonic acid isocyanate and / or vinyl trimethoxy silane, and is more preferably vinyl trimethoxy silane. In the present invention, the dewatering agent can avoid the presence of water in the system, because water reacts with isocyanate to release carbon dioxide, causing bubbles to exist in the glue during the curing process, affecting subsequent use.
[0049] Based on the mass fraction of the modified castor oil polyether polyol, the component A includes 10 to 20 parts of nano calcium carbonate, preferably 10 parts, 15 parts or 20 parts. In the present invention, the particle size D of the nano calcium carbonate is 50 Preferably, the diameter is 0.05 to 0.1 μm, and the oil absorption value is preferably 25 to 35. In a specific embodiment of the present invention, the nano calcium carbonate is preferably Huana's CCS-25. In the present invention, the nano calcium carbonate is used as a filler to strengthen and reduce costs.
[0050] Based on the mass fraction of the modified castor oil polyether polyol, the component A includes 0.01 to 0.05 parts of a defoamer, and is preferably 0.02 parts, 0.03 parts or 0.05 parts. In the present invention, the defoamer is preferably BYK A535. In the present invention, the defoamer is used to eliminate bubbles generated during the mixing and reaction of the raw materials when preparing component A.
[0051] Based on the mass fraction of the modified castor oil polyether polyol, the component A includes 0.05 to 0.1 parts of a catalyst, preferably 0.08 parts, 0.05 parts or 0.1 parts. In the present invention, the catalyst preferably includes a cyclic amine catalyst or a tin laurate catalyst, preferably dibutyltin dilaurate. In the present invention, the catalyst acts to react and cure the polyether polyol and isocyanate at a certain temperature.
[0052] The polyurethane potting adhesive provided by the present invention comprises an independently packaged component B. The component B comprises the following raw materials in parts by weight: 30-50 parts of isocyanate, 30-50 parts of polypropylene glycol, 0.5-2 parts of trimethoxysilane, 5-10 parts of fumed silica, and 0.5-1 part of flame retardant.
[0053] In parts by mass, the component B includes 30 to 50 parts of isocyanate, preferably 30 to 45 parts, and specifically preferably 40 parts, 38 parts, 30 parts or 36 parts. In the present invention, the isocyanate preferably includes alkylated isocyanate and / or polymeric isocyanate. The isocyanate more preferably includes one or more of diphenylmethane diisocyanate, toluene diisocyanate, hexamethylene diisocyanate, decamethylene diisocyanate, dodecane diisocyanate, 1,4-cyclohexane diisocyanate, 2,4-methylcyclohexane diisocyanate, isophorone diisocyanate and polymethyl polyphenyl isocyanate, and is further preferably polymethyl polyphenyl isocyanate. The polymethyl polyphenyl isocyanate is specifically preferably polymethyl polyphenyl isocyanate PM-200 of the polymeric isocyanate type.
[0054] In the present invention, PM-200 is a liquid isocyanate, and PM-200 has relatively low toxicity and relatively good stability.
[0055] Based on the mass fraction of the isocyanate, the component B includes 30 to 50 parts of polypropylene glycol, preferably 30 to 45 parts, and more preferably 40 parts, 38 parts, 30 parts or 36 parts. In the present invention, the polypropylene glycol is PPG8000.
[0056] Based on the mass fraction of the isocyanate, the component B includes 0.5 to 2 parts of trimethoxysilane, preferably 0.8 to 2 parts, and specifically preferably 1.5 parts, 1 part or 2 parts. In the present invention, the trimethoxysilane includes SilquestA-Link 597 silane and / or trimer silane. The SilquestA-Link 597 silane is SilquestA-Link597 silane from Maitu. The trimer silane is preferably purchased from Zhejiang Royal Madrid Technology Co., Ltd. In the present invention, the main structure of the trimethoxysilane is composed of trimethoxysilyl and isocyanurate structures, which can effectively improve the adhesion to various substrates, wet the substrate well, and provide the necessary heat resistance (still good at 200°C) and low volatility, thereby improving the moisture and heat resistance of the polyurethane adhesive.
[0057] Based on the mass fraction of the isocyanate, the component B includes 5 to 10 parts of fumed silica, preferably 10 parts, 8 parts, 5 parts or 6 parts. In the present invention, the fumed silica is preferably hydrophobic Evonik Aerosil R202. In the present invention, the fumed silica is used for reinforcement and adjustment of thixotropic properties.
[0058] Based on the mass fraction of the isocyanate, the component B includes 0.5 to 1 part of flame retardant, preferably 0.5 part, 0.8 part or 1 part. In the present invention, the flame retardant preferably includes an inorganic flame retardant and / or an organic flame retardant; the inorganic flame retardant preferably includes aluminum hydroxide and / or magnesium hydroxide, more preferably magnesium hydroxide. The organic flame retardant preferably includes melamine and alkyl phosphate organic matter, preferably a compound of melamine and tricresyl phosphate. The mass ratio of melamine to tricresyl phosphate is preferably 1:1.
[0059] The polyurethane potting adhesive provided by the present invention: the mass ratio of the component A to the component B is preferably 1:(1-1.2), and specifically preferably 1:1.1.
[0060] The present invention provides a method for preparing the polyurethane potting adhesive described in the above technical solution, and the preparation method of component A comprises the following steps:
[0061] The modified castor oil polyether polyol, castor oil, bisphenol A polyether polyol, dewatering agent, nano calcium carbonate, defoaming agent and catalyst are first mixed, and then polymerization reaction and curing are carried out in sequence under a first vacuum condition to obtain the component A;
[0062] The preparation method of component B comprises the following steps:
[0063] The isocyanate, polypropylene glycol, trimethoxysilane, fumed silica and flame retardant are mixed for a second time under a second vacuum condition to obtain the component B.
[0064] The present invention first mixes modified castor oil polyether polyol, castor oil, bisphenol A polyether polyol, dewatering agent, nano calcium carbonate, defoaming agent and catalyst, and then sequentially performs polymerization reaction and curing under first vacuum conditions to obtain the component A. In the present invention, before the first mixing, the present invention preferably performs physical dehydration treatment on the calcium carbonate. The first mixing preferably includes the following steps: premixing the modified castor oil polyether polyol, castor oil, bisphenol A polyether polyol and dewatering agent to obtain a premix; stirring and mixing the premix with nano calcium carbonate, defoaming agent and catalyst, and evacuating at the same time. The premixing time is preferably 10 minutes, and the premixing is preferably carried out under stirring. The vacuum degree of the first vacuum condition is preferably ≤-98kPa; the temperature of the polymerization reaction and curing is preferably room temperature, and the time is preferably 80 to 90 minutes. After the polymerization reaction and curing are completed, the present invention preferably restores to normal pressure under nitrogen conditions and cools to room temperature to obtain component A.
[0065] The present invention performs a second mixing of isocyanate, polypropylene glycol, trimethoxysilane, fumed silica and flame retardant under a second vacuum condition to obtain component B. In the present invention, the second mixing is performed under stirring. The vacuum degree of the second vacuum condition is preferably ≤-98 kPa. The temperature of the second mixing is preferably ≤40°C, and the time is preferably 20 to 30 minutes. After the first mixing is completed, the present invention preferably restores the pressure to normal pressure under nitrogen conditions and cools to room temperature to obtain component B.
[0066] The present invention provides the use of the polyurethane potting adhesive described in the above technical solution or the polyurethane potting adhesive prepared by the preparation method described in the above technical solution in the fields of adhesive for electrical appliances, adhesive for transportation vehicles, adhesive for batteries or adhesive for home decoration.
[0067] In the present invention, when the polyurethane potting glue is used, the present invention preferably mixes component A and component B of the polyurethane potting glue in a mass ratio of 1: (1-1.2), and specifically preferably 1:1.1.
[0068] The polyurethane potting glue of the present invention comprises component A and component B which are mixed when used, wherein component A comprises modified castor oil polyether polyol, castor oil, bisphenol A polyether polyol, dewatering agent, nano calcium carbonate, defoamer and catalyst; and component B comprises isocyanate, polypropylene glycol, trimethoxysilane, fumed silica and flame retardant. The polyurethane potting glue of the present invention belongs to a two-component system, and components A and B are prepared separately, have a sufficient shelf life, and can be quickly cured in a short time after mixing, provide excellent mechanical properties such as excellent shear bonding strength and extremely high strength, and will not foam, have good thermal conductivity and good resistance to moisture and heat. In addition, the raw material source of the polyurethane potting glue is simple and environmentally friendly.
[0069] In the present invention, the adhesive for transportation vehicles is preferably adhesive for packaging in the electric vehicle industry.
[0070] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0071] Example 1
[0072] The present embodiment provides a polyurethane potting adhesive and a preparation method thereof. The polyurethane potting adhesive provided by the present embodiment comprises component A and component B in a mass ratio of 1:1.1:
[0073] (1) Preparation of modified castor oil polyether polyol: 50 parts by mass of dehydrated (water content <0.05%) castor oil polyoxypropylene ether and 10 parts by mass of mercaptoethanol are added, and 5 parts by mass of azobisisobutyronitrile are added, and the mixture is heated to 100° C. and stirred for 3 h. The product is then collected and dried, and 10 parts by mass of glycerol and 0.001 parts by mass of potassium hydroxide are added, and the mixture is heated to 150° C. and reacted for 2 h under alkaline conditions to obtain modified castor oil polyether polyol.
[0074] (2) Preparation of component A: 15 parts of modified castor oil polyether polyol, 45 parts of castor oil (hydroxyl value of about 160 mgKOH / g), 20 parts of bisphenol A polyether polyol (hydroxyl value of 223-233 mgKOH / g) and 0.8 parts of dewatering agent vinyl trimethoxysilane were mixed uniformly at room temperature for 10 min. Then, 10 parts of Huana nano calcium carbonate (CCS-25), 0.02 parts of defoaming agent (Bick A535) and 0.08 parts of catalyst dibutyltin dilaurate were added, and the mixture was stirred at room temperature and vacuumed (≤-98 kPa) for 90 min. Finally, the mixture was restored to normal pressure under nitrogen and cooled to room temperature for use.
[0075] (3) Preparation of component B: 40 parts of isocyanate (polymethyl polyphenyl isocyanate PM-200), 40 parts of polypropylene glycol (PPG8000, average molecular weight 8000), 1.5 parts of trimethoxysilane (SilquestA-Link597), 10 parts of hydrophobic fumed silica (Evonik Aerosil R202) and 0.5 parts of flame retardant (melamine and tricresyl phosphate compounded in a mass ratio of 1:1) were mixed and stirred at a temperature below 40°C and vacuumed (≤-98 kPa) for 30 minutes. Finally, the mixture was restored to normal pressure under nitrogen and cooled to room temperature for use.
[0076] (4) The prepared component A and component B are mixed and potted in a mass ratio of 1:1.1 to obtain the polyurethane potting glue, and the performance of the sealant is tested according to national standards. Among them, the national standard for surface drying time is GB / T13477.5-2002, the national standard for tensile strength and elongation is GB / T528-2009, and the national standard for tensile shear strength is GB / T 7124-2008. (The detection method in the following examples and comparative examples is the same)
[0077] The test results are as follows:
[0078] The surface drying time is 58 minutes, and the curing time (60°C) is 360 minutes. After 7 days of room temperature curing, the tensile strength is 15.2 MPa, the elongation is 180%, and the tensile shear strength (aluminum-aluminum, aluminum plate thickness 2 mm) is 12.5 MPa. After 7 days at 70±2°C and relative humidity 70±5%, the tensile strength is 14.7 MPa, the elongation is 190%, and the tensile shear strength (aluminum-aluminum, aluminum plate thickness 2 mm) is 11.6 MPa.
[0079] Example 2
[0080] The present embodiment provides a polyurethane potting adhesive and a preparation method thereof. The polyurethane potting adhesive provided in the present embodiment comprises component A and component B in a mass ratio of 1:1.1:
[0081] (1) Preparation of modified castor oil polyether polyol: 50 parts by mass of dehydrated (water content <0.05%) castor oil polyoxypropylene ether and 10 parts by mass of mercaptoethanol are added, and 5 parts by mass of azobisisobutyronitrile are added, and the mixture is heated to 100° C. and stirred for 3 h. The product is then collected and dried, and 10 parts by mass of glycerol and 0.001 parts by mass of potassium hydroxide are added, and the mixture is heated to 150° C. and reacted for 2 h under alkaline conditions to obtain modified castor oil polyether polyol.
[0082] (2) Preparation of component A: 18 parts of modified castor oil polyether polyol, 42 parts of castor oil (hydroxyl value is about 160 mgKOH / g), 15 parts of bisphenol A polyether polyol (hydroxyl value is 223-233 mgKOH / g) and 0.8 parts of dewatering agent vinyl trimethoxysilane were mixed uniformly at room temperature for 10 min. Then, 10 parts of Huana nano calcium carbonate (CCS-25), 0.03 parts of defoaming agent (Bick A535) and 0.08 parts of catalyst dibutyltin dilaurate were added, and the mixture was stirred at room temperature and vacuumed (≤-98 kPa) for 90 min. Finally, the mixture was restored to normal pressure under nitrogen and cooled to room temperature for use.
[0083] (3) Preparation of component B: 38 parts of isocyanate (polymethyl polyphenyl isocyanate PM-200), 38 parts of polypropylene glycol (PPG8000, average molecular weight 8000), 1.5 parts of trimethoxysilane (trimeric silane of Zhejiang Royal Madrid Technology Co., Ltd.), 10 parts of hydrophobic fumed silica (Evonik Aerosil R202) and 0.5 parts of flame retardant (melamine and tricresyl phosphate are compounded in a mass ratio of 1:1), mixed and stirred at a temperature below 40°C and evacuated (≤-98 kPa) for 30 minutes, and finally restored to normal pressure under nitrogen and cooled to room temperature for use.
[0084] (4) The prepared component A and component B are mixed and potted in a mass ratio of 1:1.1 to obtain the polyurethane potting adhesive, and the performance of the sealant is tested in accordance with national standards.
[0085] The test results are as follows:
[0086] The surface drying time is 52 minutes, and the curing time (60°C) is 346 minutes. After 7 days of curing at room temperature, the tensile strength is 13.8 MPa, the elongation is 200%, and the tensile shear strength (aluminum-aluminum, aluminum plate thickness 2 mm) is 10.6 MPa. After 7 days at 70±2°C and relative humidity 70±5%, the tensile strength is 13.2 MPa, the elongation is 200%, and the tensile shear strength (aluminum-aluminum, aluminum plate thickness 2 mm) is 10.8 MPa.
[0087] Example 3
[0088] The present embodiment provides a polyurethane potting adhesive and a preparation method thereof. The polyurethane potting adhesive provided in the present embodiment comprises component A and component B in a mass ratio of 1:1.1:
[0089] (1) Preparation of modified castor oil polyether polyol: 50 parts by mass of dehydrated (water content <0.05%) castor oil polyoxypropylene ether and 10 parts by mass of mercaptoethanol are added, and 5 parts by mass of azobisisobutyronitrile are added, and the mixture is heated to 100° C. and stirred for 3 h. The product is then collected and dried, and 10 parts by mass of glycerol and 0.001 parts by mass of potassium hydroxide are added, and the mixture is heated to 150° C. and reacted for 2 h under alkaline conditions to obtain modified castor oil polyether polyol.
[0090] (2) Preparation of component A: 12 parts of modified castor oil polyether polyol, 48 parts of castor oil (hydroxyl value is about 160 mgKOH / g), 20 parts of bisphenol A polyether polyol (hydroxyl value is 223-233 mgKOH / g) and 1.0 part of dewatering agent vinyl trimethoxysilane were mixed uniformly at room temperature by mass for 10 min. Then 15 parts of Huana nano calcium carbonate (CCS-25), 0.02 parts of defoaming agent (Bick A535) and 0.08 parts of catalyst dibutyltin dilaurate were added, and the mixture was stirred and vacuumed (≤-98 kPa) at room temperature for 90 min. Finally, the mixture was restored to normal pressure under nitrogen and cooled to room temperature for use.
[0091] (3) Preparation of component B: 40 parts of isocyanate (diphenylmethane diisocyanate), 40 parts of polypropylene glycol (PPG8000, average molecular weight 8000), 1.0 part of trimethoxysilane (SilquestA-Link 597), 8 parts of hydrophobic fumed silica (Evonik Aerosil R202) and 0.8 parts of flame retardant (melamine and tricresyl phosphate compounded in a mass ratio of 1:1) were mixed and stirred at a temperature below 40°C and vacuumed (≤-98 kPa) for 30 minutes. Finally, the mixture was restored to normal pressure under nitrogen and cooled to room temperature for use.
[0092] (4) The prepared component A and component B are mixed and potted in a mass ratio of 1:1.1 to obtain the polyurethane potting adhesive, and the performance of the sealant is tested in accordance with national standards.
[0093] The test results are as follows:
[0094] The surface drying time is 68 minutes, and the curing time (60°C) is 375 minutes. After 7 days of curing at room temperature, the tensile strength is 12.6 MPa, the elongation is 220%, and the tensile shear strength (aluminum-aluminum, aluminum plate thickness 2 mm) is 11.5 MPa. After 7 days at 70±2°C and relative humidity 70±5%, the tensile strength is 12.7 MPa, the elongation is 220%, and the tensile shear strength (aluminum-aluminum, aluminum plate thickness 2 mm) is 11.4 MPa.
[0095] Example 4
[0096] The present embodiment provides a polyurethane potting adhesive and a preparation method thereof. The polyurethane potting adhesive provided in the present embodiment comprises component A and component B in a mass ratio of 1:1.1:
[0097] (1) Preparation of modified castor oil polyether polyol: 50 parts by mass of dehydrated (water content <0.05%) castor oil polyoxypropylene ether and 10 parts by mass of mercaptoethanol are added, and 5 parts by mass of azobisisobutyronitrile are added, and the mixture is heated to 100° C. and stirred for 3 h. The product is then collected and dried, and 10 parts by mass of glycerol and 0.001 parts by mass of potassium hydroxide are added, and the mixture is heated to 150° C. and reacted for 2 h under alkaline conditions to obtain modified castor oil polyether polyol.
[0098] (2) Preparation of component A: 20 parts of modified castor oil polyether polyol, 40 parts of castor oil (hydroxyl value is about 160 mgKOH / g), 25 parts of bisphenol A polyether polyol (hydroxyl value is 223-233 mgKOH / g) and 1.2 parts of dewatering agent vinyl trimethoxysilane are mixed uniformly at room temperature by mass for 10 min. Then, 20 parts of Huana nano calcium carbonate (CCS-25), 0.05 parts of defoaming agent (Bick A535) and 0.05 parts of catalyst dibutyltin dilaurate are added, and the mixture is stirred and vacuumized (≤-98 kPa) at room temperature for 90 min. Finally, the mixture is restored to normal pressure under nitrogen and cooled to room temperature for use.
[0099] (3) Preparation of component B: 40 parts of isocyanate (diphenylmethane diisocyanate), 40 parts of polypropylene glycol (PPG8000, average molecular weight 8000), 2.0 parts of trimethoxysilane (trimeric silane of Zhejiang Royal Madrid Technology Co., Ltd.), 10 parts of hydrophobic fumed silica (Evonik Aerosil R202) and 0.8 parts of flame retardant (magnesium hydroxide) were mixed and stirred at a temperature below 40° C. and vacuumed (≤-98 kPa) for 30 min. Finally, the mixture was restored to normal pressure under nitrogen and cooled to room temperature for use.
[0100] (4) The prepared component A and component B are mixed and potted in a mass ratio of 1:1.1 to obtain the polyurethane potting adhesive, and the performance of the sealant is tested in accordance with national standards.
[0101] The test results are as follows:
[0102] The surface drying time is 48 minutes, and the curing time (60°C) is 334 minutes. After 7 days of curing at room temperature, the tensile strength is 16.8 MPa, the elongation is 150%, and the tensile shear strength (aluminum-aluminum, aluminum plate thickness 2 mm) is 16.5 MPa. After 7 days at 70±2°C and relative humidity 70±5%, the tensile strength is 15.5 MPa, the elongation is 160%, and the tensile shear strength (aluminum-aluminum, aluminum plate thickness 2 mm) is 15.8 MPa.
[0103] Example 5
[0104] The present embodiment provides a polyurethane potting adhesive and a preparation method thereof. The polyurethane potting adhesive provided in the present embodiment comprises component A and component B in a mass ratio of 1:1.1:
[0105] (1) Preparation of modified castor oil polyether polyol: 50 parts by mass of dehydrated (water content <0.05%) castor oil polyoxypropylene ether and 10 parts by mass of mercaptoethanol are added, and 5 parts by mass of azobisisobutyronitrile are added, and the mixture is heated to 100° C. and stirred for 3 h. The product is then collected and dried, and 10 parts by mass of glycerol and 0.001 parts by mass of potassium hydroxide are added, and the mixture is heated to 150° C. and reacted for 2 h under alkaline conditions to obtain modified castor oil polyether polyol.
[0106] (2) Preparation of component A: 10 parts of modified castor oil polyether polyol, 36 parts of castor oil (hydroxyl value of about 160 mgKOH / g), 20 parts of bisphenol A polyether polyol (hydroxyl value of 223-233 mgKOH / g) and 1.0 part of dewatering agent vinyl trimethoxysilane were mixed uniformly at room temperature by mass for 10 min. Then, 15 parts of Huana nano calcium carbonate (CCS-25), 0.02 parts of defoaming agent (Bick A535) and 0.10 parts of catalyst dibutyltin dilaurate were added, and the mixture was stirred and vacuumed (≤-98 kPa) at room temperature for 90 min. Finally, the mixture was restored to normal pressure under nitrogen and cooled to room temperature for use.
[0107] (3) Preparation of component B: 30 parts of isocyanate (diphenylmethane diisocyanate), 30 parts of polypropylene glycol (PPG8000, average molecular weight 8000), 1.5 parts of trimethoxysilane (trimeric silane of Zhejiang Royal Madrid Technology Co., Ltd.), 5 parts of hydrophobic fumed silica (Evonik Aerosil R202) and 1.0 part of flame retardant (magnesium hydroxide) were mixed and stirred at a temperature below 40° C. and vacuumed (≤-98 kPa) for 30 min. Finally, the mixture was restored to normal pressure under nitrogen and cooled to room temperature for use.
[0108] (4) The prepared component A and component B are mixed and potted in a mass ratio of 1:1.1 to obtain the polyurethane potting adhesive, and the performance of the sealant is tested in accordance with national standards.
[0109] The test results are as follows:
[0110] The surface drying time is 48 minutes, and the curing time (60°C) is 388 minutes. After 7 days of curing at room temperature, the tensile strength is 11.4 MPa, the elongation is 240%, and the tensile shear strength (aluminum-aluminum, aluminum plate thickness 2 mm) is 10.8 MPa. After 7 days at 70±2°C and relative humidity 70±5%, the tensile strength is 10.5 MPa, the elongation is 250%, and the tensile shear strength (aluminum-aluminum, aluminum plate thickness 2 mm) is 10.6 MPa.
[0111] Example 6
[0112] The present embodiment provides a polyurethane potting adhesive and a preparation method thereof. The polyurethane potting adhesive provided in the present embodiment comprises component A and component B in a mass ratio of 1:1.1:
[0113] (1) Preparation of modified castor oil polyether polyol: 50 parts by mass of dehydrated (water content <0.05%) castor oil polyoxypropylene ether and 10 parts by mass of mercaptoethanol are added, and 5 parts by mass of azobisisobutyronitrile are added, and the mixture is heated to 100° C. and stirred for 3 h. The product is then collected and dried, and 10 parts by mass of glycerol and 0.001 parts by mass of potassium hydroxide are added, and the mixture is heated to 150° C. and reacted for 2 h under alkaline conditions to obtain modified castor oil polyether polyol.
[0114] (2) Preparation of component A: 15 parts of modified castor oil polyether polyol, 40 parts of castor oil (hydroxyl value is about 160 mgKOH / g), 20 parts of bisphenol A polyether polyol (hydroxyl value is 223-233 mgKOH / g) and 0.8 parts of dewatering agent vinyl trimethoxysilane are mixed uniformly at room temperature by mass for 10 min; then 15 parts of Huana nano calcium carbonate (CCS-25), 0.02 parts of defoaming agent (Bick A535) and 0.08 parts of catalyst dibutyltin dilaurate are added, stirring is continued at room temperature and vacuum is drawn (≤-98 kPa) for 90 min, and finally the mixture is restored to normal pressure under nitrogen and cooled to room temperature for use.
[0115] (3) Preparation of component B: 36 parts of isocyanate (diphenylmethane diisocyanate), 36 parts of polypropylene glycol (PPG8000, average molecular weight 8000), 1.5 parts of trimethoxysilane (SilquestA-Link 597), 6 parts of hydrophobic fumed silica (Evonik Aerosil R202) and 0.8 parts of flame retardant (melamine and tricresyl phosphate compounded in a mass ratio of 1:1) were mixed and stirred at a temperature below 40°C and vacuumed (≤-98 kPa) for 30 min. Finally, the mixture was restored to normal pressure under nitrogen and cooled to room temperature for use.
[0116] (4) The prepared component A and component B are mixed and potted in a mass ratio of 1:1.1 to obtain the polyurethane potting adhesive, and the performance of the sealant is tested in accordance with national standards.
[0117] The test results are as follows:
[0118] The surface drying time is 62 minutes, and the curing time (60°C) is 368 minutes. After 7 days of curing at room temperature, the tensile strength is 14.8 MPa, the elongation is 186%, and the tensile shear strength (aluminum-aluminum, aluminum plate thickness 2 mm) is 12.2 MPa. After 7 days at 70±2°C and relative humidity 70±5%, the tensile strength is 14.5 MPa, the elongation is 190%, and the tensile shear strength (aluminum-aluminum, aluminum plate thickness 2 mm) is 11.9 MPa.
[0119] Example 7
[0120] The present embodiment provides a polyurethane potting adhesive and a preparation method thereof. The polyurethane potting adhesive provided in the present embodiment comprises component A and component B in a mass ratio of 1:1.3:
[0121] (1) Preparation of modified castor oil polyether polyol: 50 parts by mass of dehydrated (water content <0.05%) castor oil polyoxypropylene ether and 10 parts by mass of mercaptoethanol are added, and 5 parts by mass of azobisisobutyronitrile are added, and the mixture is heated to 100° C. and stirred for 3 h. The product is then collected and dried, and 10 parts by mass of glycerol and 0.001 parts by mass of potassium hydroxide are added, and the mixture is heated to 150° C. and reacted for 2 h under alkaline conditions to obtain modified castor oil polyether polyol.
[0122] (2) Preparation of component A: 20 parts of modified castor oil polyether polyol, 40 parts of castor oil (hydroxyl value is about 160 mgKOH / g), 25 parts of bisphenol A polyether polyol (hydroxyl value is 223-233 mgKOH / g) and 1.2 parts of dewatering agent vinyl trimethoxysilane are mixed uniformly at room temperature by mass for 10 min. Then, 20 parts of Huana nano calcium carbonate (CCS-25), 0.05 parts of defoaming agent (Bick A535) and 0.05 parts of catalyst dibutyltin dilaurate are added, and the mixture is stirred and vacuumized (≤-98 kPa) at room temperature for 90 min. Finally, the mixture is restored to normal pressure under nitrogen and cooled to room temperature for use.
[0123] (3) Preparation of component B: 40 parts of isocyanate (diphenylmethane diisocyanate), 40 parts of polypropylene glycol (PPG8000, average molecular weight 8000), 2.0 parts of trimethoxysilane (trimeric silane of Zhejiang Royal Madrid Technology Co., Ltd.), 10 parts of hydrophobic fumed silica (Evonik Aerosil R202) and 0.8 parts of flame retardant (magnesium hydroxide) were mixed and stirred at a temperature below 40° C. and vacuumed (≤-98 kPa) for 30 min. Finally, the mixture was restored to normal pressure under nitrogen and cooled to room temperature for use.
[0124] (4) The prepared component A and component B are mixed and potted in a mass ratio of 1:1.1 to obtain the polyurethane potting adhesive, and the performance of the sealant is tested in accordance with national standards.
[0125] The test results are as follows:
[0126] The surface drying time is 42 minutes, and the curing time (60°C) is 320 minutes. After 7 days of room temperature curing, the tensile strength is 16.6 MPa, the elongation is 160%, and the tensile shear strength (aluminum-aluminum, aluminum plate thickness 2 mm) is 16.2 MPa. After 7 days at 70±2°C and relative humidity 70±5%, the tensile strength is 15.4 MPa, the elongation is 170%, and the tensile shear strength (aluminum-aluminum, aluminum plate thickness 2 mm) is 14.8 MPa.
[0127] Example 8
[0128] This embodiment provides a polyurethane potting adhesive and a preparation method thereof. The polyurethane potting adhesive of this embodiment is composed of component A and component B in a mass ratio of 1:1.1:
[0129] (1) Preparation of modified castor oil polyether polyol: 50 parts by mass of dehydrated (water content <0.05%) castor oil polyoxypropylene ether and 10 parts by mass of mercaptoethanol are added, and 5 parts by mass of azobisisobutyronitrile are added, and the mixture is heated to 100° C. and stirred for 3 h. The product is then collected and dried, and 10 parts by mass of glycerol and 0.001 parts by mass of potassium hydroxide are added, and the mixture is heated to 150° C. and reacted for 2 h under alkaline conditions to obtain modified castor oil polyether polyol.
[0130] (2) Preparation of component A: 15 parts of modified castor oil polyether polyol, 45 parts of castor oil (hydroxyl value of about 160 mgKOH / g), 20 parts of bisphenol A polyether polyol (hydroxyl value of 223-233 mgKOH / g) and 0.8 parts of dewatering agent vinyl trimethoxysilane were mixed uniformly at room temperature for 10 min. Then, 10 parts of Huana nano calcium carbonate (CCS-25), 0.02 parts of defoaming agent (Bick A535) and 0.08 parts of catalyst dibutyltin dilaurate were added, and the mixture was stirred at room temperature and vacuumed (≤-98 kPa) for 90 min. Finally, the mixture was restored to normal pressure under nitrogen and cooled to room temperature for use.
[0131] (3) Preparation of component B: 40 parts of isocyanate (polymethyl polyphenyl isocyanate PM-200), 40 parts of polypropylene glycol (PPG8000, average molecular weight 8000), 1.5 parts of trimethoxysilane (SilquestA-Link597), 10 parts of hydrophobic fumed silica (Evonik Aerosil R202) and 0.5 parts of flame retardant (melamine and tricresyl phosphate compounded in a mass ratio of 1:1) were mixed and stirred at a temperature below 40°C and vacuumed (≤-98 kPa) for 30 minutes. Finally, the mixture was restored to normal pressure under nitrogen and cooled to room temperature for use.
[0132] (4) The prepared component A and component B are mixed and potted in a mass ratio of 1:1.1 to obtain the polyurethane potting adhesive, and the performance of the sealant is tested in accordance with national standards.
[0133] The test results are as follows:
[0134] The surface drying time is 48 minutes, and the curing time (60°C) is 342 minutes. After 7 days of curing at room temperature, the tensile strength is 15.0 MPa, the elongation is 180%, and the tensile shear strength (aluminum-aluminum, aluminum plate thickness 2 mm) is 12.8 MPa. After 7 days at 70±2°C and relative humidity 70±5%, the tensile strength is 14.7 MPa, the elongation is 180%, and the tensile shear strength (aluminum-aluminum, aluminum plate thickness 2 mm) is 12.6 MPa.
[0135] The following comparative experiment is conducted by replacing different castor oil polyols on the market (source: BASF Sovermol 805 and Ito Oil URICAC009).
[0136] Comparative Example 1
[0137] This comparative example provides a polyurethane potting adhesive and a preparation method thereof. The component A and component B of the polyurethane potting adhesive provided in this comparative example are composed in a mass ratio of 1:1.1:
[0138] (1) Preparation of component A: 15 parts of BASF Sovermol 805, 40 parts of castor oil (hydroxyl value of about 160 mgKOH / g), 20 parts of bisphenol A polyether polyol (hydroxyl value of 223-233 mgKOH / g) and 0.8 parts of dewatering agent vinyl trimethoxysilane were mixed at room temperature for 10 min. Then, 15 parts of Huana nano calcium carbonate (CCS-25), 0.02 parts of defoaming agent (Bick A535) and 0.08 parts of catalyst dibutyltin dilaurate were added. The mixture was stirred at room temperature and vacuumed (≤-98 kPa) for 90 min. Finally, the mixture was restored to normal pressure under nitrogen and cooled to room temperature for use.
[0139] (2) Preparation of component B: 36 parts of isocyanate (diphenylmethane diisocyanate), 36 parts of polypropylene glycol (PPG8000, average molecular weight 8000), 1.5 parts of trimethoxysilane (trimeric silane of Zhejiang Royal Madrid Technology Co., Ltd.), 6 parts of hydrophobic fumed silica (Evonik Aerosil R202) and 0.8 parts of flame retardant (melamine and tricresyl phosphate are compounded in a mass ratio of 1:1) are mixed and stirred at a temperature below 40°C and vacuumed (≤-98 kPa) for 30 minutes. Finally, the mixture is restored to normal pressure under nitrogen and cooled to room temperature for use.
[0140] (3) The prepared component A and component B are mixed and potted in a mass ratio of 1:1.1 to obtain the polyurethane potting adhesive, and the performance of the sealant is tested in accordance with national standards.
[0141] The test results are as follows:
[0142] The surface drying time is 65 minutes, and the curing time (60°C) is 354 minutes. After 7 days of room temperature curing, the tensile strength is 14.6 MPa, the elongation is 190%, and the tensile shear strength (aluminum-aluminum, aluminum plate thickness 2 mm) is 13.2 MPa. After 7 days at 70±2°C and relative humidity 70±5%, the tensile strength is 13.8 MPa, the elongation is 190%, and the tensile shear strength (aluminum-aluminum, aluminum plate thickness 2 mm) is 12.4 MPa.
[0143] Comparative Example 2
[0144] This comparative example provides a polyurethane potting adhesive and a preparation method thereof. The component A and component B of the polyurethane potting adhesive provided in this comparative example are composed in a mass ratio of 1:1.1:
[0145] (1) Preparation of component A: 15 parts of Ito Oil URICAC009, 40 parts of castor oil (hydroxyl value of about 160 mgKOH / g), 20 parts of bisphenol A polyether polyol (hydroxyl value of 223-233 mgKOH / g) and 0.8 parts of dewatering agent vinyl trimethoxysilane were mixed by mass and stirred evenly at room temperature for 10 min; then 15 parts of Huana nano calcium carbonate (CCS-25), 0.02 parts of defoaming agent (Bick A535) and 0.08 parts of catalyst dibutyltin dilaurate were added, and the mixture was stirred and vacuumed (≤-98 kPa) at room temperature for 90 min. Finally, the mixture was restored to normal pressure under nitrogen and cooled to room temperature for use.
[0146] (2) Preparation of component B: 36 parts of isocyanate (diphenylmethane diisocyanate), 36 parts of polypropylene glycol (PPG8000, average molecular weight 8000), 1.5 parts of trimethoxysilane (trimeric silane of Zhejiang Royal Madrid Technology Co., Ltd.), 6 parts of hydrophobic fumed silica (Evonik Aerosil R202) and 0.8 parts of flame retardant (melamine and tricresyl phosphate are compounded in a mass ratio of 1:1) are mixed and stirred at a temperature below 40°C and vacuumed (≤-98 kPa) for 30 minutes. Finally, the mixture is restored to normal pressure under nitrogen and cooled to room temperature for use.
[0147] (3) The prepared component A and component B are mixed and potted in a mass ratio of 1:1.1 to obtain the polyurethane potting adhesive, and the performance of the sealant is tested in accordance with national standards.
[0148] The test results are as follows:
[0149] The surface drying time is 58 minutes, and the curing time (60°C) is 342 minutes. After 7 days of room temperature curing, the tensile strength is 15.6 MPa, the elongation is 180%, and the tensile shear strength (aluminum-aluminum, aluminum plate thickness 2 mm) is 13.8 MPa. After 7 days at 70±2°C and relative humidity 70±5%, the tensile strength is 14.2 MPa, the elongation is 196%, and the tensile shear strength (aluminum-aluminum, aluminum plate thickness 2 mm) is 13.2 MPa.
[0150] From the test results of the polyurethane potting glue products prepared with the modified castor oil polyether polyol produced by Royal Madrid Technology in Comparative Example 1, Comparative Example 2 and Examples 1 to 8, it can be seen that different castor oil-based polyols have achieved relatively good technical effects, and the tensile strength, elongation and shear strength after 7 days of room temperature curing are basically at the same level. There is not much fluctuation in the performance comparison after aging, indicating that its moisture and heat resistance is also relatively excellent. In particular, its excellent shear bonding strength can be used for rapid bonding to prevent falling off, which can meet the bonding and fitting requirements of home decoration tiles or floors, indicating that the polyurethane potting glue prepared with the modified castor oil polyether polyol produced by Royal Madrid Technology in the embodiment of the present invention can meet market demand.
[0151] The following control experiment was conducted by changing the mass percentages of different raw materials or process conditions in the polyurethane potting adhesive formulation beyond those in the examples.
[0152] Comparative Example 3
[0153] This comparative example provides a polyurethane potting adhesive and a preparation method thereof. The component A and component B of the polyurethane potting adhesive provided in this comparative example are composed in a mass ratio of 1:1.1:
[0154] (1) Preparation of modified castor oil polyether polyol: 50 parts by mass of dehydrated (water content <0.05%) castor oil polyoxypropylene ether and 10 parts by mass of mercaptoethanol are added, and 5 parts by mass of azobisisobutyronitrile are added, and the mixture is heated to 100° C. and stirred for 3 h. The product is then collected and dried, and 10 parts by mass of glycerol and 0.001 parts by mass of potassium hydroxide are added, and the mixture is heated to 150° C. and reacted for 2 h under alkaline conditions to obtain modified castor oil polyether polyol.
[0155] (2) Preparation of component A: 15 parts of modified castor oil polyether polyol, 45 parts of castor oil (hydroxyl value of about 160 mgKOH / g) and 20 parts of bisphenol A polyether polyol (hydroxyl value of 223-233 mgKOH / g) were mixed uniformly at room temperature for 10 min. Then, 10 parts of Huana nano calcium carbonate (CCS-25), 0.02 parts of defoaming agent (Bick A535) and 0.08 parts of catalyst dibutyltin dilaurate were added. The mixture was stirred at room temperature and vacuumed (≤-98 kPa) for 90 min. Finally, the mixture was restored to normal pressure under nitrogen and cooled to room temperature for use.
[0156] (3) Preparation of component B: 40 parts of isocyanate (polymethyl polyphenyl isocyanate PM-200), 40 parts of polypropylene glycol (PPG8000, average molecular weight 8000), 1.5 parts of trimethoxysilane (SilquestA-Link597), 10 parts of hydrophobic fumed silica (Evonik Aerosil R202) and 0.5 parts of flame retardant (melamine and tricresyl phosphate compounded in a mass ratio of 1:1) were mixed and stirred at a temperature below 40°C and vacuumed (≤-98 kPa) for 30 minutes. Finally, the mixture was restored to normal pressure under nitrogen and cooled to room temperature for use.
[0157] (4) The prepared component A and component B are mixed and potted in a mass ratio of 1:1.1 to obtain the polyurethane potting adhesive, and the performance of the sealant is tested in accordance with national standards.
[0158] In Comparative Example 3, the amount of dehydrating agent is removed, so water reacts with isocyanate to release carbon dioxide, causing bubbles to exist in the glue during the curing process, affecting subsequent use. In addition, calcium carbonate is physically dehydrated before use to meet the use requirements.
[0159] The test results are as follows:
[0160] The surface drying time is 52 minutes, and the curing time (60°C) is 360 minutes. After 7 days of room temperature curing, there are bubbles on the surface and inside of the colloid, which seriously affects the mechanical properties and causes them to decline. The tensile strength is 10.2 MPa, the elongation is 120%, and the tensile shear strength (aluminum-aluminum, aluminum plate thickness 2 mm) is 9.5 MPa. After 7 days at 70±2°C and relative humidity 70±5%, the tensile strength is 9.4 MPa, the elongation is 110%, and the tensile shear strength (aluminum-aluminum, aluminum plate thickness 2 mm) is 8.6 MPa.
[0161] Comparative Example 4
[0162] This comparative example provides a polyurethane potting adhesive and a preparation method thereof. The component A and component B of the polyurethane potting adhesive provided in this comparative example are composed in a mass ratio of 1:0.8:
[0163] (1) Preparation of modified castor oil polyether polyol: 50 parts by mass of dehydrated (water content <0.05%) castor oil polyoxypropylene ether and 10 parts by mass of mercaptoethanol are added, and 5 parts by mass of azobisisobutyronitrile are added, and the mixture is heated to 100° C. and stirred for 3 h. The product is then collected and dried, and 10 parts by mass of glycerol and 0.001 parts by mass of potassium hydroxide are added, and the mixture is heated to 150° C. and reacted for 2 h under alkaline conditions to obtain modified castor oil polyether polyol.
[0164] (2) Preparation of component A: 15 parts of modified castor oil polyether polyol, 45 parts of castor oil (hydroxyl value of about 160 mgKOH / g), 20 parts of bisphenol A polyether polyol (hydroxyl value of 223-233 mgKOH / g) and 0.8 parts of dewatering agent vinyl trimethoxysilane were mixed uniformly at room temperature for 10 min. Then, 10 parts of Huana nano calcium carbonate (CCS-25), 0.02 parts of defoaming agent (Bick A535) and 0.08 parts of catalyst dibutyltin dilaurate were added, and the mixture was stirred at room temperature and vacuumed (≤-98 kPa) for 90 min. Finally, the mixture was restored to normal pressure under nitrogen and cooled to room temperature for use.
[0165] (3) Preparation of component B: 20 parts of isocyanate (polymethyl polyphenyl isocyanate PM-200), 40 parts of polypropylene glycol (PPG8000, average molecular weight 8000), 1.5 parts of trimethoxysilane (SilquestA-Link597), 10 parts of hydrophobic fumed silica (Evonik Aerosil R202) and 0.5 parts of flame retardant (melamine and tricresyl phosphate compounded in a mass ratio of 1:1) were mixed and stirred at a temperature below 40°C and vacuumed (≤-98 kPa) for 30 minutes. Finally, the mixture was restored to normal pressure under nitrogen and cooled to room temperature for use.
[0166] (4) The prepared component A and component B are mixed and potted in a mass ratio of 1:0.8 to obtain the polyurethane potting adhesive, and the performance of the sealant is tested in accordance with national standards.
[0167] In Comparative Example 4, the amount of isocyanate used is reduced. Reducing the amount of isocyanate is equivalent to the inability of component A and component B to react completely, resulting in insufficient cross-linking points, which causes the subsequent product performance to fail to achieve the desired effect.
[0168] The test results are as follows:
[0169] The surface drying time is 77 minutes, and the curing time (60°C) is 400 minutes. After 7 days of room temperature curing, the tensile strength is 10.2 MPa, the elongation is 210%, and the tensile shear strength (aluminum-aluminum, aluminum plate thickness 2 mm) is 7.5 MPa. After 7 days at 70±2°C and relative humidity 70±5%, the tensile strength is 9.7 MPa, the elongation is 220%, and the tensile shear strength (aluminum-aluminum, aluminum plate thickness 2 mm) is 7.6 MPa.
[0170] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A polyurethane potting adhesive, characterized in that: It includes component A and component B which are packaged separately; The component A comprises the following raw materials in parts by weight: 10-20 parts of modified castor oil polyether polyol, 30-50 parts of castor oil, 10-25 parts of bisphenol A polyether polyol, 0.5-1.2 parts of dewatering agent, 10-20 parts of nano calcium carbonate, 0.01-0.05 parts of defoaming agent, and 0.05-0.1 parts of catalyst; the modified castor oil polyether polyol is obtained by reacting castor oil polyoxypropylene ether with mercaptoethanol and glycerol in sequence; The component B comprises the following raw materials in parts by weight: 30-50 parts of isocyanate, 30-50 parts of polypropylene glycol, 0.5-2 parts of trimethoxysilane, 5-10 parts of fumed silica, and 0.5-1 part of flame retardant.
2. The polyurethane potting adhesive according to claim 1, characterized in that: The mass ratio of component A to component B is 1:(1-1.2).
3. The polyurethane potting adhesive according to claim 1 or 2, characterized in that: The hydroxyl value of the modified castor oil polyether polyol is 480-500 mgKOH / g; the preparation method of the modified castor oil polyether polyol comprises the following steps: Castor oil polyoxypropylene ether, mercaptoethanol and azo initiator are mixed to carry out polymerization reaction to obtain a mercapto-modified product; The mercapto-modified product, glycerol and an inorganic base compound are mixed to carry out an ester exchange reaction to obtain the modified castor oil polyether polyol.
4. The polyurethane potting adhesive according to claim 3, characterized in that: The water content of the castor oil polyoxypropylene ether is less than 0.05%, and the mass ratio of the castor oil polyoxypropylene ether to mercaptoethanol is (1-5):1; the azo initiator is azobisisobutyronitrile, and the mass ratio of the castor oil polyoxypropylene ether to the azo initiator is (1-10):1; the temperature of the polymerization reaction is 110±5°C, and the time is 3±0.5h.
5. The polyurethane potting adhesive according to claim 3, characterized in that: The mass ratio of the castor oil polyoxypropylene ether to the glycerol is (1-5):1; the inorganic base is an alkali metal hydroxide; the temperature of the transesterification reaction is 150±5°C, and the time is 2±0.5h.
6. The polyurethane potting adhesive according to claim 1 or 2, characterized in that: The hydroxyl value of the castor oil is 150-170 mgKOH / g; The bisphenol A polyether polyol has a hydroxyl value of 223 to 233 mgKOH / g; The dewatering agent includes p-toluenesulfonic acid isocyanate and / or vinyl trimethoxy silane; The particle size D of the nano calcium carbonate 50 0.05~0.1μm, oil absorption value is 25~35; The defoamer includes BYK A535; The catalyst includes a cyclic amine catalyst or a tin laurate catalyst.
7. The polyurethane potting adhesive according to claim 1 or 2, characterized in that: The isocyanate includes one or more of diphenylmethane diisocyanate, toluene diisocyanate, hexamethylene diisocyanate, decamethylene diisocyanate, dodecane diisocyanate, 1,4-cyclohexane diisocyanate, 2,4-methylcyclohexane diisocyanate, isophorone diisocyanate and polymethyl polyphenyl isocyanate; The polypropylene glycol is PPG8000; The trimethoxysilane includes SilquestA-Link 597 silane and / or trimer silane; The fumed silica is hydrophobic Evonik Aerosil R202; The flame retardant includes inorganic flame retardant and / or organic flame retardant; the inorganic flame retardant includes aluminum hydroxide and / or magnesium hydroxide; the organic flame retardant includes melamine and alkyl phosphate organic matter.
8. The method for preparing the polyurethane potting adhesive according to any one of claims 1 to 7, characterized in that: The preparation method of component A comprises the following steps: The modified castor oil polyether polyol, castor oil, bisphenol A polyether polyol, dewatering agent, nano calcium carbonate, defoaming agent and catalyst are first mixed, and then polymerization reaction and curing are carried out in sequence under a first vacuum condition to obtain the component A; The preparation method of component B comprises the following steps: The isocyanate, polypropylene glycol, trimethoxysilane, fumed silica and flame retardant are mixed for a second time under a second vacuum condition to obtain component B.
9. The preparation method according to claim 8, characterized in that: The vacuum degree of the first vacuum condition and the second vacuum condition is ≤-98 kPa; the temperature of the polymerization reaction and curing is room temperature, and the time is 80 to 90 minutes; The temperature of the second mixing is ≤40° C. and the time is 20 to 30 minutes.
10. Use of the polyurethane potting adhesive according to any one of claims 1 to 7 or the polyurethane potting adhesive prepared by the preparation method according to claim 8 or 9 in the fields of adhesive for electrical appliances, adhesive for transportation vehicles, adhesive for batteries or adhesive for home decoration.
